Investigations on Stability and Long-term Behaviour of AFm Phases at Higher Temperatures by Powder Diffraction Methods - Götz-Neunhoeffer, Friedlinde; Pöllmann, Herbert (Materials Science Forum, 1996)
Immobilisation and solidification of pollutants can be achieved by adding cement to the waste products or by mixing adequate proportions of industrial waste products as flue gas desulfurization products, fly-ashes, contaminated sludges etc. The resulting stabilised product of this treatment is containing different reservoir minerals intimately intergrown with non reactive material. The solidified waste containing the immobilised pollutants itself can be used as an "Inner Barrier System" [1] of a waste dump. For this application the solidification products have to be stable under the physico-chemical conditions in a waste dump. In this study the long-term behaviour of the formed reservoir minerals of the AFm-type (Al2O3-Fe2O3-monophases) was evaluated by X-ray investigations at higher temperatures.
UnivIS-Import:2015-03-05:Pub.1996.nat.dgeo.IGM.LM.invest_0
Keywords: AFm Phases; Halogenides; Immobilisation; Lamellar Calcium Ferrate Hydrates; Reservoir Minerals; X-Ray Diffraction at Higher Temperatures